Educational Model and Practice of STEM Education+Creator - Li, Yan; Zhang, Qiaoliang; Feng, Wenfang; Kang, Haibin; Bao, Zheshi; Wang, Song (Educational sciences : theory & practice, 2018)
There are few achievements in the research of STEM educational theory and practice in China and there exists a lack of systematic course system, activity design framework and resource support in STEM education, so this study probes into the localization of STEM education based on the present situation in China. In the educational model of “STEM education + creator”, this study finds out the model of integrating STEM education into the talent cultivation process by means of creator space. Then through the method of evaluating students’ problem-solving ability, this study explores the influence of STEM course on students’ problem-solving ability and explores a new way of thinking of reform.